CASES BASED LEARNING DAN DIRECT INSTRUCTION UNTUK MENINGKATKAN KEAKTIFAN SERTA HASIL BELAJAR STUDI PADA MAHASISWA MATA KULIAH AKUNTANSI KEUANGAN LANJUTAN (An-Nisbah: Jurnal Ekonomi Syariah, 2016)
This research aims to improve activity and learning outcomes of students in the subject of Advanced Financial Accounting especially the material headquarters and branch offices by integrating the model of cases based learning and direct instruction. In the model case based learning, students are faced with a real case to be solved. Therefore, it stimulates their activities in learning. While,the model of direct instruction is a declarative and procedural learning process that makes students more understand the material. The results of this study show that there is the increase of activity and learning outcomes of students, evidenced by the increase of value and percentage of learning outcomes in the course of Advanced Financial Accounting.Keywords: Cases Based Learning, Direct Instruction, Activity, andLearning Outcomes of Students.